Impact of early discharge on the newborn - Rita Sousa; Inês Foz; Bruno Sanches; Susana Marcelino; Armandina Horta; Deolinda Matos; Paulo Calhau; Anselmo Costa (Publicaciones Permanyer, 2023)
Introduction and objectives: In Western countries, the average length of stay in the postpartum period for newborns without complications follows a decreasing trend. The aim of the present study was to evaluate the impact of early discharge on the newborn, particularly regarding the risk of hospital readmission. Methods: Cross-sectional study of newborns with early discharge born in a level II hospital with differentiated perinatal support, between June 2021 and May 2022. Clinical and demographic data were obtained from the analysis of the patient's medical records and phone contact. Early discharge was considered to be the interval less than or equal to 48h between birth and discharge of the newborn. Results: From the 508 newborns enrolled in our study, 217 (42.7%) had an early discharge and 291 (57.3%) had a standard length of stay. The mean length of stay was 2.3 days (1.8 early discharge vs 2.6 discharge after 48h). In the comparative analysis (early discharge vs. discharge after 48h) there was no statistically significant association between early discharge and hospital readmission rate (0.5% vs 1.4%, p = 0.399), emergency observation rate (13.4% vs 10%, p = 0.233) or abandonment of exclusive breastfeeding within 15-days after postpartum discharge (22.7% vs 28.4%, p = 0.180). The results were similar for the subgroup of NB discharged within 39h. Instrumented delivery, birth weight less than 2500g, prematurity and phototherapy were factors that contributed to longer length of stay. Conclusion: In this study, early discharge was not associated with a higher risk for the newborn. Regarding the clinical and social advantages, this approach should be considered and supported by adequate surveillance in primary health care.